Desempenho cognitivo em pacientes com Transtorno de Personalidade Borderline com e sem histórico de tentativas de suicídio - Pastore, Edilson (Universidade do Vale do Rio dos Sinos, 2012)
The objective of the present Master's thesis was to investigate the cognitive performance of participants with Borderline Personality Disorder (BPD) with and without a history of suicide attempts. The review of the literature and the empirical results of this study were described in a theoretical article and an empirical article about BPD, suicide, and cognitive functions. The theoretical article consisted of an asystematic and critical review of the literature on the disorder, addressing the characteristics of the development of this pathology and discussing its cognitive aspects. This review of the literature focused on executive functions, especially: attention, concentration, decision making, organization of thought, and working memory, suggesting that deficits in these functions may be risk factors for suicide in patients with this diagnosis. The conclusions of the theoretical article indicate the presence of specific cognition deficits, mainly in the executive functions of the participants diagnosed with BPD. We discussed recent articles on the topic and approached the need and relevance of further studies and similar findings. The empirical article presents the results of a quantitative, cross-sectional and comparative study conducted with a sample of 82 patients (M=31.80, SD=0.96) diagnosed with BPD and admitted to a psychiatric clinic in Porto Alegre, Rio Grande do Sul, Brazil. The Wechsler Adult Intelligence Scale (WAIS III), the Barratt Impulsiveness Scale, the Beck Suicide Scale, the FAST scale, and a questionnaire containing sociodemographic data were administered to the participants. There was no significant difference in terms of total IQ among the participants with BPD with and without a history of suicide attempts, suggesting that the heterogeneity of patients with this diagnosis, as well as the large number of comorbidities in this population, may have been important factors to explain this result. However, we found that patients with a history of suicide attempts have higher index of impulsivity, especially patients younger than 30 years, leading to the conclusion that individuals of this age group with BPD may be more vulnerable to both suicide and suicide attempts. Although there was no significant difference between the groups, the means on the Wechsler Scale (cognitive functions) in terms of total IQ were within the mean level of cognitive functioning with an IQ of 92 for the group of patients with a history of suicide attempt and 96 for the group without suicide attempts. Levels of impulsivity were higher in patients with a history of suicide attempts; in addition, the degree of adaptation measured by the FAST Scale was lower in the same group. These results explain aspects of BPD and provide the opportunity of developing appropriate therapeutic methods. The need for further studies on this topic was also evidenced by the lack of neuropsychological research or studies on cognitive functions in patients diagnosed with BPD in Brazil.
Keywords: Transtorno de Personalidade Borderline; Desempenho cognitivo; Funções executivas; Suicídio; Impulsividade; Borderline personality disorder; Cognitive performance; Executive functions; Suicide; Impulsivity; ACCNPQ::Ciências Humanas::Psicologia